1995
DOI: 10.1093/jnci/87.8.587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diets Containing Eicosapentaenoic or Docosahexaenoic Acid on Growth and Metastasis of Breast Cancer Cells in Nude Mice

Abstract: Future dietary intervention trials designed to reduce the risk of recurrence in the postsurgical breast cancer patient should include the evaluation of eicosapentaenoic acid and docosahexaenoic acid supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
1
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(151 citation statements)
references
References 0 publications
10
137
1
3
Order By: Relevance
“…Alternatively, diets containing high levels of n-3 PUFAs, mainly EPA and DHA, have been shown to inhibit development of several carcinogen-induced and transplantable cancers (Karmali et al, 1984;Carroll and Braden, 1985a;Jurkowski and Cave, 1985;Cohen et al, 1993;Kinoshita et al, 1994;Rose et al, 1995). With regard to the promotive or inhibitory effects of PUFAs, several authors have drawn attention to the dietary imbalance of n-3 and n-6 PUFAs (Karmali, 1987a;Karmali et al, 1989;Kromhout, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, diets containing high levels of n-3 PUFAs, mainly EPA and DHA, have been shown to inhibit development of several carcinogen-induced and transplantable cancers (Karmali et al, 1984;Carroll and Braden, 1985a;Jurkowski and Cave, 1985;Cohen et al, 1993;Kinoshita et al, 1994;Rose et al, 1995). With regard to the promotive or inhibitory effects of PUFAs, several authors have drawn attention to the dietary imbalance of n-3 and n-6 PUFAs (Karmali, 1987a;Karmali et al, 1989;Kromhout, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that rural Japanese (Iso et al, 1989) and Greenland Eskimos (Sinclair, 1981), who exhibit low breast cancer rates, consume a larger amount of dietary n-3 PUFAs, compared with high-risk Americans (Sinclair, 1981;Cohen et al, 1993). Fish oils rich in n-3 PUFAs, mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been shown to inhibit tumour development in some animal models (Karmali et al, 1984;Carroll and Braden, 1985a;Jurkowski and Cave, 1985; Cohen et al, 1993;Kinoshita et al, 1994;Rose et al, 1995). However, several investigators have found that the inhibitory effect of n-3 PUFAs was apparent when the n-31n-6 ratio ranged from 1:1 to 1:2 (Abou- El-Ela et al, 1989;Cohen et al, 1993;Noguchi et al, 1995a), indicating that the ratio of n-3 to n-6 PUFAs preventive agents in breast cancer, but a large amount of dietary n-3 PUFAs would be required for breast cancer prevention and treatment.…”
mentioning
confidence: 99%
“…Alterations in cell membrane phospholipid synthesis and composition, membrane fluidity and order, and lipid-dependent pharmacology are common during tumorigenesis and may play a key role in determining the metastatic behavior of tumor cells (3)(4)(5)(6). It is well established that lipid structural order in membranes is largely determined by cholesterol and sphingomyelin content and by the degree of saturation of the phospholipid fatty acyl chains (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…LA has been shown to stimulate proliferation of this cell line (Rose and Connolly, 1989), and this was dependent on the products of lipoxygenase rather than cyclooxygenase pathways (Rose and Connolly, 1990). When this cell line was transplanted into nude mice, diets rich in n-3 PUFAs reduced both tumour growth and metastasis, and this was found to correlate with a three-to four-fold reduction in 12-and 15-HETE production (Rose et al, 1995). Growth of the androgen-unresponsive prostatic cancer cell line, PC-3, was shown to be stimulated in vitro by LA, while DU-145, which is also androgen unresponsive, showed no growth response to LA .…”
Section: Discussionmentioning
confidence: 96%
“…Another agent inhibiting tumour proliferation, eicosapentaenoic acid (EPA) has been shown to reduce the tumour concentration of 12-and 15-HETE, while the level of 5-HETE was unaffected (Rose et al, 1995). These results suggest that inhibition of 12-and/or 15-lipoxygenases may be most important for tumour growth inhibition, and some 5-lipoxygenase inhibitors may show anti-tumour activity as a result of cross-reactivity towards these pathways.…”
Section: Discussionmentioning
confidence: 99%